(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: In terms of health outcomes for both mother and child, breast milk is the best first diet for newborns. For working postnatal women, expressed breast milk is a healthier option than formula milk. The research objective was explore the problems of working mothers regarding breastfeeding and to assess the status of knowledge and practice regarding expressed breast milk feeding among working mothers.Materials and Methods: In this study, an exploratory survey design was adopted. A total of 80 postnatal working women were chosen by a non-probability convenient sampling method from three universities. The observation problems checklist, structured knowledge questionnaire, and self-reported practice checklist were used to examine working mothers knowledge and practice related expressed breast milk feeding in order to collect data for the research project.Result: According to the findings of the study, the majority of mothers 50(62.5%) had concerns with employers treating them differently because they chose to express breast milk at work. The sample's knowledge score on expressed breast milk feeding is 48(60%) have very poor knowledge and 41 (51.2%) have moderate practice for expressed breast milk feeding. The relationship between sociodemographic factors and the question on do you have 6 months of maternity leave? shows educational level of mothers obtained chi square value ꭓ2=7.275 and p=0.026 and the relationship between sociodemographic factors and question on do you feel comfortable to expressing milk in work place? shows that educational level of mothers obtained chi square value ꭓ2=10.228 and p=0.006 was found statistically significant association. The value of “r” was 0.049. It was statistically significant at the 0.01 level of significance. So that researcher found that there is a positive correlation between knowledge and practice score of expressed breast milk feeding.Conclusion: Researcher concluded that, most people have a moderate understanding and there is a good association between knowledge and practice of expressed breast milk feeding. This demonstrates that as mothers' knowledge improves, their practice level regarding expressed breast milk feeding improves as well.